KEBIJAKAN FORMULASI TINDAK PIDANA JUDI ONLINE DALAM BINGKAI HUKUM POSITIF DI INDONESIA - Eko Ari Wibowo (JURNAL SUMBER HUKUM, 2024)
A criminal act is basically an act that is prohibited or recommended by law due to certain circumstances. An act is said to be a criminal act when the act has been formulated in a statutory regulation and ratified by the legislative body together with the government. The regulation of online gambling as a type of criminal act is one of the results of policy formulation in Indonesia. This is stated in Law Number 11 of 2008 concerning Information and Electronic Transactions. This journal article contains information about the development of criminal acts of gambling and analysis of policy formulation of criminal acts of online gambling. The approach method used is a normative juridical method. The research results in this paper state that basically gambling, which was previously done manually or directly, has now experienced a new mutation resulting from the expansion of electronic-based criminal acts. So that the criminal formulation policy now follows current developments, with the legal aim of eradicating crime, especially in the field of online gambling crimes. Keywords; Formulation Policy, Criminal act, Online Gambling.